PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERBASIS INKUIRI TERBIMBING MATERI ARCHAEABACTERIA DAN EUBACTERIA UNTUK PESERTA DIDIK KELAS X-MIA SEMESTER I SMA NEGERI 2 PARE KABUPATEN KEDIRI - Ertiningsih Ertiningsih (Universitas Sebelas Maret, 2014)
Pursuant to requirement analysis in SMA 2 Pare known that still found teacher which not yet educative by participant its knowledge construction, peripheral of used study not yet according to requirement and items require to be developed by peripheral of study matching with educative participant potency and requirement, may even exist teacher which not yet compiled by xself peripheral of its study. According to fact and requirement hence target of this development and research is to yield peripheral of study of Biology base on inkuiri guided for the items of Archaeabacteria and of Eurbacteria educative by participant class of X-MIA in SMA 2 Pare Sub-Province of Kediri.Research type is development and research pursuant to model development of Borg & Gall and which consist of 10 phase. Research data obtained from instrument validasi development of peripheral of study by development expert, items expert, and teacher and also educative participant enquette. There is two data type to be obtained by that is quantitative data and data qualitative. Data of Kuantitaif analysed by calculating score and reconciled with the tables of elegibility criterion and revise product. Data qualitative in the form of comment and suggestion used to revise product.Research and development which have shown result of for example: (1) according to assessment by development expert, items expert and Biological teacher in assessment of elegibility of peripheral at criterion very competent and needn't revise; (2) individual test to readers of Handout and LKPD reside in at criterion very competent and needn't revise (score average 3,6); (3) small group test in assessment is understanding of concept 17% educative participant is not complete, and 83,0% residing in complete criterion; (4) assessment to erudite skill 100% complete (>80); result of assessment pluck activity reside in criterion 100% complete (assess lowest 81,3); result of attitude observation is 86,18% showing attitude very good, and 13,9% showing good attitude; (5) tired study keterlaksanaan of average 3,85 this means all step can follow and answered to by entire all educative participant. Keywords: Learning Biology Material, Guided In Inquiry, Handout